Crystal structure of the haloalkane dehalogenase from Sphingomonas paucimobilis UT26 - Marek, J; Vévodová, J; Smatanová, I K; Nagata, Y; Svensson, L A; Newman, J; Takagi, M; Damborský, J (Biochemistry, 2000)
The haloalkane dehalogenase from Sphingomonas paucimobilis UT26 (LinB) is the enzyme involved in the degradation of the important environmental pollutant gamma-hexachlorocyclohexane. The enzyme hydrolyzes a broad range of halogenated cyclic and aliphatic compounds. Here, we present the 1.58 A crystal structure of LinB and the 2.0 A structure of LinB with 1,3-propanediol, a product of debromination of 1,3-dibromopropane, in the active site of the enzyme. The enzyme belongs to the alpha/beta hydrolase family and contains a catalytic triad (Asp108, His272, and Glu132) in the lipase-like topological arrangement previously proposed from mutagenesis experiments. The LinB structure was compared with the structures of haloalkane dehalogenase from Xanthobacter autotrophicus GJ10 and from Rhodococcus sp. and the structural features involved in the adaptation toward xenobiotic substrates were identified. The arrangement and composition of the alpha-helices in the cap domain results in the differences in the size and shape of the active-site cavity and the entrance tunnel. This is the major determinant of the substrate specificity of this haloalkane dehalogenase.
Keywords: Computer Simulation; Crystallization; krystalizace; hydrolasy; Models, Molecular; substrátová specifita; Sphingomonas; počítačová simulace; Bromine; brom; Xanthobacter; vazebná místa; Substrate Specificity; krystalografie rentgenová; Rhodococcus; Hydrolases; Binding Sites; molekulární modely; Crystallography, X-Ray